RISK FACTORS AND PREDICTION OF MIOCARDIAL INFARCTION IN MALES OF DIFFERENT AGE - Qosimov Iqboljon Sodiqjon ogli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
To conduct complex evaluation of MI risk factors in men taking their agespecific qualities, and to invent prediction calculator of MI based upon the data obtained.Totally, 12 males with Q and non-Q MI included, at the age 45-74 y. o., mean age — 58,9±0,6 y. o. In all patients we assessed clinical and anamnestic data, parameters of lipid, carbohydrate metabolism, sex hormones levels, CRP, levels of hypodynamia, depression and anxiety via questionnaires.To predict the risk of MI with statistical methods, a calculator was invented, which make it to estimate the probability of MI development in a patient taken their age-specific risks.